2021
DOI: 10.5489/cuaj.7621
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the identification and management of metastatic prostate cancer patients with DNA repair gene alterations in the Canadian context

Abstract: Olaparib is the first Health Canada-approved agent in metastatic prostate cancer to use a companion diagnostic to identify alterations in BRCA1, BRCA2, or ATM. As olaparib is introduced, clinicians must learn to access and interpret germline and somatic next-generation sequencing (NGS) results, and how to manage affected patients who appear to have distinct clinical features. The traditional model of referring patients to a hereditary cancer clinic (HCC) for germline testing is likely impractical in this disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…[24][25][26] Historically, patients were referred to genetics service or hereditary cancer clinic for genetic counselling and testing. 27,28 Mainstreaming is an alternative method for performing germline CUAJ -Special Feature Saad et al Controversial areas in the management of advanced PCa 10 © 2023 Canadian Urological Association testing and affords clinicians (oncologists, urologists, oncology surgeons) the advantage of ordering testing after pre-test counselling and taking consent from patients, rather than referring to another provider (e.g., genetic counselor, clinical geneticist). Physicians acknowledged the desire for mainstream genetic testing, however, in Canada, this approach is limited to Ontario, Quebec, and British Columbia, with the turnaround time for mainstreamed tests ranging 3-6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Historically, patients were referred to genetics service or hereditary cancer clinic for genetic counselling and testing. 27,28 Mainstreaming is an alternative method for performing germline CUAJ -Special Feature Saad et al Controversial areas in the management of advanced PCa 10 © 2023 Canadian Urological Association testing and affords clinicians (oncologists, urologists, oncology surgeons) the advantage of ordering testing after pre-test counselling and taking consent from patients, rather than referring to another provider (e.g., genetic counselor, clinical geneticist). Physicians acknowledged the desire for mainstream genetic testing, however, in Canada, this approach is limited to Ontario, Quebec, and British Columbia, with the turnaround time for mainstreamed tests ranging 3-6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 In the past decades, NGS was widely used to apply diagnosis, treatment, and drug resistance to disease. 21 , 22 This study aimed to monitor gene mutation profiling and evaluate relationships between landscapes of gene mutation and the prognosis significances of renal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Inevitably, patients with advanced disease will develop metastatic castration-resistant prostate cancer (mCRPC), with current standard-of-care systemic therapy options including androgen receptor pathway inhibitors (ARPIs; i.e., abiraterone acetate, enzalutamide); taxanebased chemotherapies (docetaxel, cabazitaxel); and bone-targeted therapies (radium-223). [5][6][7][8][9][10][11][12][13][14] Furthermore, alterations in genes associated with homologous recombination repair (HRR), such as BRCA1 and BRCA2, have been shown to confer sensitivity to poly adenosine diphosphateribose polymerase (PARP) inhibition in mCRPC. [15][16][17][18][19][20][21][22] Consequently, the PARP inhibitor, olaparib, was approved by Health Canada for use in patients with mCRPC harbouring a BRCA1, BRCA2-or ATM genetic alteration, who have progressed after at least one line of ARPIs, based upon the results of the Phase III PROfound trial.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Consequently, the PARP inhibitor, olaparib, was approved by Health Canada for use in patients with mCRPC harbouring a BRCA1, BRCA2-or ATM genetic alteration, who have progressed after at least one line of ARPIs, based upon the results of the Phase III PROfound trial. 13,15,16 Genomic studies have reported that approximately 20%-30% of metastatic PCa (mPCa) patients harbour HRR pathway alterations; 13,16,17,[23][24][25][26][27] approximately 10%-15% being germline (inherited) in origin and 20%-25% somatic (acquired) 14 in origin. Response to standard-of-care therapies, such as ARPIs, also differs in mPCa patients with HRR gene alterations, in contrast to patients with wild-type HRR status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation